The Influence Of English Song As Learning Materials Towards The Students' Pronunciation - Dewi Yulyanti; Slamet Wahyudi Yulianto; Muhammad Anjar Nugraha (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2019)
This research investigated whether or not there is the influence of English song towards the student’s pronunciation. This research used a quantitative method. Research design is an experimental class and control class, two classes were selected from eleventh-grade students at SMAN 1 Ciasem Subang. The Quasi-Experimental Research was conducted in four meetings. The data were obtained by observing the teaching and learning process, test, questionnaire, and interviewing the students. The research result of the analysis quantitative and qualitative data were as follows. The analysis of quantitative data, mean score of pre-test in the experimental class was 14.44. While the mean score in the control class was 14.58. Furthermore, the mean score of the post-test in the experimental class was 82.98. While the mean score post-test in the control class was 60.56. Based on the result, the experimental class students’ score on post-test were better in which the mean = 82.89 than their scores on pre-test the mean = 60.56 . in addition, the two-tailed value of p was 0.000 which was lower than 0.05 . in conclusion, the calculation of paired t-test showed that there was a significant difference between the pre-test and post-test scores of experimental group. The analysis of qualitative data show that used English song influence through students’ pronunciation by observing the teaching and learning process, test, questionnaire, and interviewing the students. The students were more confident and were not afraid of making mistakes when pronunciation.